Individual Company Bankruptcy Based On The Bankruptcy Law - Mochamad Cholil; Ni Made Yordha Ayu Astiti; Maghfirah Aliefia; Zakia Fhadillah (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
After the promulgation of Law Number 11 of 2020 Concerning Job Creation, it has been made possible to form a new legal entity, namely an Individual Company. These changes are referred to in the provisions of Article 109 of the Job Creation Law, which contains several changes to Law Number 40 of 2007 concerning Limited Liability Companies. The government also contains further regulations regarding the existence of an individual company as a legal entity in Government Regulation Number 8 of 2021 concerning Company Authorized Capital and Registration of the Establishment, Amendment and Dissolution of Companies that Meet the Criteria for Micro and Small Enterprises. However, the presence of Government Regulation Number 8 of 2021 does not comprehensively regulate several existing legal issues. Therefore, this research was conducted to analyze the problem. Issues related to whether or not individual companies can apply for bankruptcy at the Commercial Court. If this is possible, the creditor as referred to in the provisions of Article 2 of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Debt Payment can naturally become a party involved in a bankruptcy case filed against an Individual Company. This type of research is legal research using statutory and conceptual approaches. The results of this study indicate that an individual company is not necessarily easy to apply for bankruptcy, It is hoped that the existence of an individual company will be able to drive the movement of the economy. Thus, although it is possible to apply for bankruptcy against an individual company, to resolve problems related to general confiscations, a civil lawsuit should be filed in the District Court.